Envelhecimento, exerc??cio f??sico e controle postural: uma an??lise sobre a a????o do exerc??cio f??sico na preserva????o do controle postural em idosas - Tavares, Juliana Teles (2016)
The practice of physical exercise has been an important alternative to minimize the effects of age on postural control, however, there is a possibility that interruption of training (detraining) may contribute to the performance of static balance return to pre- training. The objective of this study was to analyze the action of multicomponent physical exercise on the postural control of the elderly and its effects after the period of detraining. The postural control of 31 women aged 60 to 80 years was evaluated in six different conditions on a force platform in the following conditions: static position with and without visual afferent (open eye and closed eye); Static position with the use of a foam on the platform with and without visual gauge; Static position with visual and auditory stimulation with and without the use of foam on the force platform. These variables were used to analyze the effects of two types of training for the elderly, being divided into two groups: Multicomponent Group (GM): training with strength, aerobic, balance and flexibility exercises and Control Group (CG): training with Aerobic exercise and flexibility. All participants underwent a 16-week training period, three times a week (total of 48 sessions). The postural control was analyzed before and after the training period and with 6 weeks of training. In the analysis of variance (ANOVA) it was possible to verify that the training provided significant (F = 24.72, p <0.0001) in the oscillation frequency between the groups (multicomponent group vs control group). The multicomponent group showed a significant decrease in the oscillation frequency after the training period (p <0.05), but the values observed after the training period were not different from those observed in the pre-training (p> 0.05). In this study it was possible to observe that sixteen-week training with multi-component exercises improves the postural control of elderly women. However, these effects are not maintained after a six-week period of detraining.